To Dance with Time: A Victoria River Aboriginal Study - Rose, Deborah Bird (The Australian journal of anthropology, 2000)
Drawing on research with Aboriginal people in the Victoria River District of Australia, this paper explores time in patterns of motion and pause. Taking Cath Ellis's insight that some Aboriginal musicians posses a faculty of ‘perfect time’, and that the meshing of rhythms and other patterns in music has the effect of altering perceptions and understandings of time, I explore rhythmic patterns in four domains—nomadology, ecology, dance and cosmology. I suggest that the cosmogonic and temporal effects of rhythm in motion are capable of becoming performative events because they link the rhythms of ecological, social and ritual domains. Such events implicate the ephemeral motion and temporality of the world in a continuing flow of becoming, and implicate the continuity of flow in the actions of the ephemeral.